The Development of Interactive Multimedia Using Articulate Storyline 3 for Teaching Standard Unit Volume Measurement to Fourth Grade Elementary School Students : Pengembangan Multimedia Interaktif Berbasis Articulate Storyline 3 Materi Pengukuran Volume Satuan Baku Kelas 4 Sekolah Dasar - Hanantha, Dhirta Satria; Wahid Ibnu Zaman; Zainal Afandi (IJPSE Indonesian Journal of Primary Science Education, 2025)
The issue of students’ learning outcomes in mathematics, particularly in the topic of standard unit volume measurement, which have not yet met the minimum completeness criteria, has become a problem in Grade 4 at SDN 7 Sugihwaras. Based on data triangulation, the main contributing factor is the abstract nature of the material, which leads to low student interest. In addition, teacher-centered learning further reduces students’ engagement in the learning process. This study aims to develop interactive multimedia to improve students’ learning outcomes. The research is a Research and Development (R&D) study using the Plomp development model. The Plomp model consists of five phases: preliminary investigation, design, realization/construction, test, evaluation and revision, and implementation. he results of the expert validation show that the interactive multimedia developed using Articulate Storyline 3 received a score of 92.3% from the subject matter expert and 96% from the media expert, both falling into the "Highly Valid" category. In terms of practicality, student response questionnaires yielded a score of 100%. Limited trials resulted in a score of 86.25, while wider trials yielded 87.83. Thus, this interactive multimedia meets the criteria of validity, practicality, and effectiveness, and can be used to improve students' learning outcomes.